Fox fur ecological nitration process based on non-formaldehyde synergistic tanning and ultrasonic assistance
Patent Information
- Application Number
- CN202611127980.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]为了解决现有技术中存在的某种或某些技术问题,本申请的目的在于提供一种基于无醛协同鞣制与超声波辅助的狐狸皮生态硝制工艺,能够解决现有生皮因厚薄不均而导致化学药品渗透不均以及内部存在甲醛残留风险的问题,使皮毛具有良好的防虫、抗菌效果,且耐久性好,降低生产成本
1、基于现有工艺进行改进,通过增加超声波/微波装置后,将“超声波/微波物理场”引入传统的裘皮硝制化学过程,解决了化学渗透慢的难题;
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of fur production, specifically to an eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance. Background Technology
[0002] Currently, when tanning fox raw pelts, we have been using the method described in patent "CN201610410677.1 A Tanning Process for Making Fur from Fox Raw Pellets". However, the current process has the following problems: First, a small amount of formaldehyde needs to be added during the leather washing step to improve the tanning effect. However, the use of formaldehyde in the tanning process poses a risk of formaldehyde residue, which does not meet increasingly stringent environmental protection standards. Furthermore, although the existing process achieves water recycling, the wastewater from the washing process is highly polluting and can easily cause water pollution. Secondly, currently, the main method for washing hides is prolonged soaking. However, the uneven thickness of animal hides can lead to uneven penetration of chemicals, resulting in "over-tanning on the surface and insufficient penetration inside." This is especially true for the thicker parts of fox hides, such as the head and tail. Due to the large difference in hide thickness, the finished product may appear "rigid" or "loose."
[0003] Third, as a high-end fur, fox fur is prone to attracting moths. Traditional insect-proofing processes mostly involve post-treatment spraying, which has poor durability. Summary of the Invention
[0004] In order to solve one or more technical problems existing in the prior art, the purpose of this application is to provide an eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance. This process can solve the problems of uneven chemical penetration and formaldehyde residue risk caused by uneven thickness of existing raw hides. It gives the fur good insect-proof and antibacterial effects, good durability, and reduces production costs.
[0005] To solve the aforementioned technical problems, this application adopts the following technical solution: An eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasound-assisted tanning, the process steps of which include: S1. Pretreatment: Ultrasonic cleaning is added to the degreasing step to remove oil and dirt deep in the pores by utilizing the cavitation effect of the ultrasonic cleaning. S2, Formaldehyde-free tanning: Soak the softened leather in tanning water that has been reused for no more than one week, with the temperature controlled at 33-35℃. Add salt, zirconium-aluminum-plant polyphenol synergistic tanning agent, penetrant, and soda ash until the pH value is 4-4.5. Remove the leather after soaking overnight. S3. Microwave-assisted fatliquoring and insect-proof modification: After tanning, the fur is successively turned, washed, and rinsed before fatliquoring. During the fatliquoring stage, pulsed microwaves are used for assistance, and a special fatliquoring agent containing natural pyrethroid microcapsules is added. S4. Plush Shaping and Brightening: The fat-added leather is compounded with nano-TiO2 dispersion and whitening / bluening agent to whiten white fox and bluen blue fox respectively; S5. Drying.
[0006] Preferably, in the degreasing step, the temperature is controlled at 40-45℃, and an ultrasonic generator is turned on to perform synchronous wave ultrasonic cleaning at a frequency of 25-28kHz, shortening the processing time to 1.5-2 hours.
[0007] Preferably, in step S2, during the formaldehyde-free tanning process, while adding the zirconium-aluminum-plant polyphenol synergistic tanning agent, low-frequency ultrasonic treatment is activated. The ultrasonic frequency is 20~30kHz, and the treatment time is 30~60 minutes, in order to promote the penetration of the tanning agent into the deep layers of the leather.
[0008] Preferably, in the formaldehyde-free tanning process of step S2, the amount of salt added is 20~30 g / L, the amount of zirconium-aluminum-plant polyphenol synergistic tanning agent added is 8%~15% of the hide weight, and the amount of penetrant added is 0.5~1.0 g / L.
[0009] Preferably, the zirconium-aluminum-plant polyphenol synergistic tanning agent is composed of the following components: Zirconium-based components are used to provide metal coordination ability; Aluminum-based components are used to form complexes with plant polyphenols and to regulate the tanning process; Plant polyphenol components, acting as cross-linking bridging molecules, connect metal ions and collagen; And a scavenging agent for controlling the hydrolysis rate of the zirconium-based component.
[0010] Preferably, the mass ratio of the zirconium-based component, the aluminum-based component, the plant polyphenol component, and the scavenger is 2.0~3.0:0.8~1.5:2.0~4.0:0.5~1.0.
[0011] Preferably, the zirconium-based component is zirconium chloride or zirconium sulfate; the aluminum-based component is basic aluminum chloride or aluminum sulfate.
[0012] Preferably, the plant polyphenol component is derived from at least one extract of green tea by-products, gallnut, or mulberry bark, and has a solid content >80%.
[0013] Preferably, the masking agent is sodium citrate or sodium lactate.
[0014] Preferably, in step S3, the pyrethroid microcapsule content in the special fatliquoring agent is 5-8%; the specific parameters of the pulsed microwave assistance are: microwave frequency 2450MHz, intermittent pulse mode, and control of the leather plate temperature not exceeding 45℃.
[0015] Preferably, the amount of nano-TiO2 dispersion added in step S4, the plush shaping and brightening step, is 0.5~0.7%.
[0016] Preferably, in step S2, the tanning water is tanning waste liquid that has been reused for no more than one week, and it is filtered before reuse. The zirconium content in the reused tanning liquid is controlled at 0.5~1.5g / L.
[0017] Preferably, in step S2, the process of adjusting the pH value with soda ash is to add it in three parts, with an interval of 20 minutes between each addition, until the final pH value is stable at 4.0-4.5.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Based on the existing process, improvements were made by adding an ultrasonic / microwave device to introduce the "ultrasonic / microwave physical field" into the traditional fur tanning chemical process, thus solving the problem of slow chemical penetration. 2. The use of "zirconium-aluminum-plant polyphenol synergistic tanning agent" to replace the original "modified aldehyde tanning agent" solves the problem of formaldehyde residue risk, while also reducing wastewater pollution; 3. The combination of "pyrethroid microcapsules + nano TiO2 dispersion" for insect control can give fur good insect-proof and antibacterial effects, and good durability. 4. Introducing ultrasonic cleaning during the degreasing stage after meat removal utilizes cavitation to remove oil and dirt deep within the pores, resulting in a more thorough cleaning. 5. By adding microwave / ultrasonic devices, the problem of uneven chemical penetration caused by uneven thickness of raw hides is solved. In particular, for the thicker parts of fox hides, such as the head and tail, the reaction time is greatly shortened and the amount of chemicals used is reduced, which can reduce production costs. Detailed Implementation
[0019] The following detailed description further illustrates this application. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0020] An eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasound-assisted tanning, the process steps of which include: S1. Pretreatment: Ultrasonic cleaning is added to the degreasing step to remove oil and dirt deep in the pores by utilizing the cavitation effect of the ultrasonic cleaning. S2, Formaldehyde-free tanning: Soak the softened leather in tanning water that has been reused for no more than one week, with the temperature controlled at 33-35℃. Add salt, zirconium-aluminum-plant polyphenol synergistic tanning agent, penetrant, and soda ash until the pH value is 4-4.5. Remove the leather after soaking overnight. S3. Microwave-assisted fatliquoring and insect-proof modification: After tanning, the fur is successively turned, washed, and rinsed before fatliquoring. During the fatliquoring stage, pulsed microwaves are used for assistance, and a special fatliquoring agent containing natural pyrethroid microcapsules is added. S4. Plush Shaping and Brightening: The fat-added leather is compounded with nano-TiO2 dispersion and whitening / bluening agent to whiten white fox and bluen blue fox respectively; S5. Drying.
[0021] Improvements to existing processes, including the addition of ultrasonic / microwave devices, introduce an ultrasonic / microwave physical field into the traditional fur tanning chemical process, solving the problem of slow chemical penetration. The use of a zirconium-aluminum-plant polyphenol synergistic tanning agent instead of the original modified aldehyde tanning agent eliminates the risk of formaldehyde residue and reduces wastewater pollution. A combination of pyrethroid microcapsules and nano-TiO2 dispersion is employed for insect control, resulting in excellent insect-repellent and antibacterial effects and good durability. Ultrasonic cleaning is introduced during the degreasing stage after meat removal, utilizing cavitation to remove deep-seated oils and dirt from the pores for a more thorough cleaning. The addition of microwave / ultrasonic devices addresses the uneven chemical penetration caused by varying hide thickness, particularly for the thicker areas of fox pelts like the head and tail, significantly shortening reaction time and reducing chemical usage, thus lowering production costs.
[0022] A further improvement is made in that, during the degreasing step, the temperature is controlled at 40-45℃, and an ultrasonic generator is turned on to perform synchronous wave ultrasonic cleaning at a frequency of 25-28kHz, reducing the processing time to 1.5-2 hours.
[0023] Introducing ultrasonic cleaning during the degreasing stage after meat removal utilizes cavitation to remove oil and dirt deep within the pores, resulting in a more thorough cleaning. This significantly improves efficiency, reducing processing time from several hours or even longer with traditional methods to 1.5-2 hours. This means more batches of pelts can be processed per unit time, directly reducing production cycles and energy costs. Simultaneously, degreasing is more thorough, effectively removing deep-seated oils and dirt from hair follicles compared to traditional soaking and stirring. Utilizing the "cavitation effect" of ultrasound, these stubborn stains are powerfully removed, resulting in a more thorough cleaning. Residual oils on the fur are a major obstacle to the penetration of tanning agents, fatliquoring agents, and other chemicals. Thorough degreasing lays a good foundation for subsequent tanning processes, ensuring that chemicals penetrate the pelt evenly and quickly. This effectively solves the problem of "over-tanning on the surface and insufficient penetration inside" caused by uneven thickness in fox pelts, resulting in softer, more uniform pelts and avoiding defects such as "stiffness" or "looseness."
[0024] A further improvement is made in step S2, the formaldehyde-free tanning process, where a zirconium-aluminum-plant polyphenol synergistic tanning agent is added while a low-frequency ultrasonic treatment is initiated. The ultrasonic frequency is 20-30 kHz and the treatment time is 30-60 minutes to promote the penetration of the tanning agent into the deep layers of the leather.
[0025] In the formaldehyde-free tanning process, fox fur is typically thicker at the head and tail, and thinner on the belly. In traditional processes, tanning agents often first bind to the surface fibers (surface over-tanning), resulting in a hardened surface while the tanning agent hasn't penetrated the interior (internal incomplete tanning). However, by using ultrasound for 30-60 minutes to force the tanning agent to migrate deeper, ensuring consistent tanning results across both thick and thin areas, the finished leather has a uniform softness throughout, avoiding stiffness or cracks. Because the tanning agent penetrates deeper and binds more evenly, the finished product has a higher shrinkage temperature (Ts), better wet heat stability, and looser fibers, resulting in a fuller feel. The tanning agent is also absorbed more thoroughly, reducing residue in the waste liquid. Ultrasound waves at a frequency of 20-30 kHz generate cavitation bubbles in the tanning solution. The micro-jet streams and shock waves generated when the bubbles burst act like countless miniature "pumps," forcibly pushing the tanning liquid into the microfiber gaps of the leather fibers, overcoming the resistance of tanning agent molecules (especially the large molecular complex of zirconium-aluminum-polyphenol) to diffuse into the leather interior.
[0026] A further improvement is made in that, during the aldehyde-free tanning process in step S2, the amount of salt added is 20~30 g / L, the amount of zirconium-aluminum-plant polyphenol synergistic tanning agent added is 8%~15% of the hide weight, and the amount of penetrant added is 0.5~1.0 g / L.
[0027] The tanning solution contains 20-30 g / L of salt and 0.5-1.0 g / L of penetrant. The salt helps prevent spoilage, inhibits hide swelling, and aids in tanning agent penetration. However, too low a salt concentration can lead to hide swelling and uneven tanning agent penetration; too high a concentration inhibits the binding of tanning agents to collagen, reducing the tanning effect. Non-ionic penetrants (such as fatty alcohol polyoxyethylene ethers) are used to avoid precipitation of anionic and metallic tanning agents. Too low a concentration results in uneven tanning agent penetration, while too high a concentration reduces the surface tension of the bath excessively, potentially damaging the fur. Therefore, the concentration is generally controlled at 0.5-1.0 g / L. The dosage of the zirconium-aluminum-plant polyphenol synergistic tanning agent varies depending on hide thickness. The upper limit for thick hides is 15%, and the lower limit is 8% for thin hides. Additionally, in winter when water temperatures are low, the penetrant dosage can be increased (up to 1.0 g / L) to promote penetration.
[0028] A further improvement is made to the zirconium-aluminum-plant polyphenol synergistic tanning agent, which is composed of the following components: a zirconium-based component, which provides metal coordination ability; an aluminum-based component, which forms a complex with plant polyphenols and regulates the tanning process; a plant polyphenol component, which acts as a cross-linking bridging molecule to connect metal ions and collagen; and a scavenging agent, which controls the hydrolysis rate of the zirconium-based component.
[0029] Fox fur is characterized by its thin pelt, tightly woven fibers, and thick coat of fur. Fox fur is typically used to make high-end clothing (such as collars and shawls), requiring extremely high fullness and softness of the pelt. Traditional pure zirconium tanning, while involving high shrinkage temperatures, easily leads to a stiff, rigid pelt. Aluminum-based components (such as basic aluminum chloride) have smaller molecules and penetrate very quickly, primarily filling the spaces between the leather fibers. They effectively "spread" the fibers and maintain a loose texture. This compensates for the stiffness of zirconium-tanned leather, resulting in a fuller, softer, and more elastic fox fur. Zirconium-based components (Zr...) 4 (⁺) It possesses extremely strong coordination ability, forming very strong polynuclear complexes with the carboxyl groups on collagen fibers, providing extremely high shrinkage temperatures (typically above 95℃). Simultaneously, plant polyphenols act as macromolecular "bridgers," further cross-linking zirconium, aluminum, and leather fibers to form a dense three-dimensional network, significantly improving the leather's resistance to washing and perspiration. The biggest challenge in formaldehyde-free tanning is usually insufficient shrinkage temperature (Ts), causing the leather to easily shrink and harden when exposed to hot water or high-temperature ironing. This formula perfectly solves this problem.
[0030] In leather chemistry, zirconium and aluminum salts are highly sensitive to pH and temperature. Traditionally, it was believed that vigorous physical agitation or energy input (such as ultrasound) could cause localized instability in the metal complexes, even leading to premature precipitation (i.e., the tanning agent precipitates on the surface before penetrating, resulting in "surface over-tanning"). However, scavenging agents (such as sodium citrate) can bind with zirconium ions, stabilizing the metal complexes, while ultrasound provides the penetration impetus. This combination of "chemical stabilization + physical acceleration" breaks the technical prejudice that "metal tanning cannot be vigorously assisted," achieving rapid and uniform tanning. Delaying the hydrolysis of zirconium salts and their binding to leather fibers allows the tanning agent ample time to penetrate to the deepest parts of the hide. Subsequently, the intervention of plant polyphenols further stabilizes this penetration, ensuring uniform tanning throughout the entire fox pelt. Avoiding the fatal defects of "surface over-tanning (hardening and cracking) and internal under-tanning (hardening and loosening)" that are common in traditional tanning methods, this formula, used to prepare fox pelts, imparts an excellent feel of "lightness, thinness, and softness."
[0031] Meanwhile, fox fur (especially white fox and silver fox) requires extremely high color standards for the fur, and traditional chrome tanning easily causes the fur to become dull and yellow. Plant polyphenols themselves have certain antioxidant and natural whitening / brightening effects. When combined with aluminum salts, they not only prevent the pelt from yellowing but also make the fox fur whiter and shinier, reducing the need for subsequent bleaching and dyeing chemicals.
[0032] A further improvement is made whereby the mass ratio of the zirconium-based component, the aluminum-based component, the plant polyphenol component, and the masking agent is 2.0~3.0:0.8~1.5:2.0~4.0:0.5~1.0; the zirconium-based component is zirconium chloride or zirconium sulfate; the aluminum-based component is basic aluminum chloride or aluminum sulfate; the plant polyphenol component is derived from at least one extract of green tea by-products, gallnut, or mulberry bark, and has a solid content >80%; and the masking agent is sodium citrate or sodium lactate.
[0033] Zirconium-based components are crucial for providing the shrinkage temperature (Ts). Below 2.0 parts, the cross-linking density is insufficient, and Ts cannot reach above 95℃; above 3.0 parts, excess zirconium ions cannot be effectively stabilized by polyphenols and masking agents, leading to premature precipitation on the leather surface, resulting in "over-tanning, hardening, and stiffness." A zirconium-based component of 2.0~3.0 parts ensures sufficient heat resistance for fox fur without compromising its softness due to excessive amounts. Aluminum-based components penetrate extremely quickly; if used in large quantities, they will bind extensively in the shallow layers of the leather, hindering zirconium penetration to deeper layers. 0.8~1.5 parts of aluminum-based components perfectly fill the fiber gaps, maintaining looseness without interfering with the deep penetration of zirconium, thus giving the leather a full and soft feel without sacrificing the deep cross-linking effect of zirconium. Polyphenols have large molecular weights, requiring a sufficient amount to form a complete "zirconium-polyphenol-collagen" three-dimensional cross-linked network. Below 2.0 parts, the cross-linking network is incomplete, resulting in poor water resistance; above 4.0 parts, excessive polyphenols will form insoluble precipitates with metal ions, clogging the fiber gaps. When the plant polyphenol component is between 2.0 and 4.0 parts, it can significantly improve the water resistance and perspiration resistance of the leather, while giving the fur a natural brightening effect. Conversely, if the amount of saturating agent is below 0.5 parts, the slow-release effect is insufficient, and zirconium precipitates rapidly on the surface; if the amount is above 1.0 parts, the slow release is excessive, and the tanning reaction is too slow, making it difficult to achieve the ideal Ts value even with extended tanning time. When it is between 0.5 and 1.0 parts, it ensures that the tanning agent achieves the best balance between "penetration" and "binding," resulting in uniform tanning throughout the entire fox pelt.
[0034] The zirconium-based component uses either zirconium chloride or zirconium sulfate, both of which are highly water-soluble zirconium salts that can rapidly dissociate into Zr in the tanning solution. 4 ⁺ provides a sufficient source of metal ions for subsequent coordination with polyphenols and collagen. Zirconium chloride has higher solubility and is suitable for low-temperature, rapid tanning; zirconium sulfate has better slow-release properties and is suitable for long-term tanning. The availability of either increases process flexibility.
[0035] Aluminum-based components: Basic aluminum chloride or aluminum sulfate are used, which contain various polynuclear aluminum hydroxy complexes, offering superior permeability and filling properties compared to ordinary aluminum salts. Aluminum sulfate, on the other hand, is less expensive and more widely available. Both options are available, balancing performance and cost-effectiveness.
[0036] Plant polyphenols are extracted from green tea by-products, gallnut, or horse chestnut bark. Among them, green tea by-products are rich in catechin polyphenols, with a moderate molecular weight, good permeability, and natural antioxidant and antibacterial properties, which help preserve fur for a long time.
[0037] Gallnut: Rich in gallnut tannins (high content), it has a strong ability to complex with metal ions, forming the densest cross-linked network and providing the highest water resistance.
[0038] Masang leather: Rich in condensed tannins, it has a good affinity with collagen fibers, resulting in the softest and fullest feel after tanning. It can meet the tanning requirements of different grades of fox fur.
[0039] The solid content of plant polyphenol extracts directly affects the tanning effect. If the solid content is too low, it means that the extract contains a large amount of water and other impurities. These impurities will dilute the effective concentration of the tanning solution, affecting the tanning efficiency, and may even introduce unnecessary impurities that interfere with the stability of the tanning reaction. Limiting the solid content to >80% ensures the purity and effective concentration of the polyphenol components, making the tanning reaction controllable and repeatable, and ensuring stable product quality.
[0040] The masking agent is sodium citrate or sodium lactate, both of which are food-grade safe organic acid salts and are effective against Zr. 4 ⁺ It has moderate chelating ability. Sodium citrate has a slightly stronger chelating ability than sodium lactate, making it suitable for areas with thicker skin; sodium lactate has a slightly weaker chelating ability, making it suitable for areas with thinner skin, such as the abdomen. Both can be selected to allow for fine-tuning based on the specific condition of the skin.
[0041] A further improvement is made in step S3, wherein the content of pyrethroid microcapsules in the special fatliquoring agent is 5-8%; and the specific parameters of the pulsed microwave assistance are: microwave frequency 2450MHz, intermittent pulse mode, and control of the leather plate temperature not exceeding 45℃.
[0042] Natural pyrethroids, derived from pyrethrum flowers, are low in toxicity to humans and animals and environmentally friendly. Compared to traditional synthetic insecticides (such as DDT and organophosphates), they do not persist in the environment. Natural pyrethroids are easily decomposed and deactivated under high temperatures, metal ions, air, and ultraviolet light. If added directly to fatliquoring agents, their active ingredients will rapidly degrade during the tanning process, and the insect-repellent effect will only last for a short time. Microencapsulation technology encapsulates pyrethroids through a wall material, isolating them from the external environment and significantly reducing the decomposition rate. Studies have shown that microencapsulated pyrethroids exhibit significantly improved stability below 250°C, and the loading rate only decreased by 6.2% after 4 months of storage at 4°C in the dark. This means that finished fox fur can continuously and slowly release insect-repellent components during wear and storage, greatly extending the insect-repellent effectiveness. When the pyrethroid microcapsule content is below 5%, the microcapsule loading in the leather is insufficient, failing to form an effective insect-repellent concentration gradient, and the insect-repellent effect will be greatly reduced. When the pyrethroid microcapsule content is greater than 8%, it will lead to raw material waste and increased costs. On the other hand, excessive microcapsule loading may affect the softness and feel of the leather, making the fur stiff.
[0043] A further improvement is made by adding 0.5-0.7% of the nano-TiO2 dispersion in step S4, the step of setting and brightening the plush texture.
[0044] Nano-TiO2 possesses an extremely high refractive index, enabling it to efficiently scatter and reflect visible light. When evenly applied to fur, it produces a strong "optical whitening" and "brightening" effect, giving fox fur a whiter, purer, and more lustrous visual appearance. This eliminates the slight yellowing caused by aging or previous treatments, achieving a more natural and longer-lasting brightening effect than traditional organic fluorescent whitening agents. Simultaneously, the dense inorganic film formed by the nanoparticles on the hair cuticle surface increases the stiffness and firmness of the hair, making the fur smoother and less prone to deformation after styling.
[0045] A further improvement is made in step S2, wherein the tanning water is tanning waste liquid that has been reused for no more than one week, and is filtered before reuse, and the zirconium content in the reused tanning liquid is controlled at 0.5~1.5g / L; the process of adjusting the pH value with soda ash is to add it in three parts, with an interval of 20 minutes between each addition, and the final pH value is stabilized at 4.0-4.5.
[0046] In traditional fox fur tanning processes, tanning wastewater contains residual zirconium salts, aluminum salts, scavengers, and plant polyphenols. Direct discharge not only wastes resources but also requires costly wastewater treatment (removal of the heavy metal zirconium is expensive). Filtering and reusing the wastewater can reduce tanning wastewater discharge by more than 50% at the source, significantly lowering environmental treatment costs. Controlling the zirconium content in the reused tanning liquid to 0.5-1.5 g / L ensures that it is not rendered unusable due to excessively low zirconium content, nor does excessive zirconium content lead to excessive tanning agents and over-tanning of the hides in new batches. Tanning wastewater contains organic matter such as proteins and fats dissolved from the hides. If left for too long (more than one week), these organic substances will decompose under normal temperature, causing the wastewater to become foul-smelling, discolored, and its pH value to shift, severely affecting tanning quality after reuse (e.g., discoloration and off-odors on the hides). Therefore, it should generally not be left for more than one week. The waste liquid contains solid impurities such as skin flakes, hair fragments, and silt. Filtration ensures the cleanliness of the reused liquid, making its quality close to that of freshly prepared liquid.
[0047] Soda ash is a strong alkali; if added in large quantities at once, the pH of the tanning solution will rise sharply in a short period. In the zirconium-aluminum-polyphenol system, the increase in pH directly accelerates the hydrolysis of zirconium ions and their binding reaction with collagen fibers. If the pH rises suddenly, zirconium ions will instantly hydrolyze and precipitate in large quantities on the surface of the leather, forming a dense "shell" that blocks pores and fiber gaps, preventing the tanning agent from penetrating deeper—this is the typical case of "over-tanning on the surface, but not penetrating inside." Adding it in three stages, with 20-minute intervals between each addition, allows the pH to rise slowly in a stepwise manner. This gives the zirconium ions sufficient time to penetrate deeper at each pH step before continuing the reaction, thus achieving uniform tanning from the inside out.
[0048] The above embodiments are merely preferred embodiments of this application and should not be construed as limiting the scope of protection of this application. Any non-substantial changes and substitutions made by those skilled in the art based on this application shall fall within the scope of protection claimed by this application.
Claims
1. An eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance, characterized in that: The process steps include: S1. Pretreatment: Ultrasonic cleaning is added to the degreasing step to remove oil and dirt deep in the pores by utilizing the cavitation effect of the ultrasonic cleaning. S2, Formaldehyde-free tanning: Soak the softened leather in tanning water that has been reused for no more than one week, with the temperature controlled at 33-35℃. Add salt, zirconium-aluminum-plant polyphenol synergistic tanning agent, penetrant, and soda ash until the pH value is 4-4.
5. Remove the leather after soaking overnight. S3. Microwave-assisted fatliquoring and insect-proof modification: After tanning, the fur is successively turned, washed, and rinsed before fatliquoring. During the fatliquoring stage, pulsed microwaves are used for assistance, and a special fatliquoring agent containing natural pyrethroid microcapsules is added. S4. Plush Shaping and Brightening: The fat-added leather is compounded with nano-TiO2 dispersion and whitening / bluening agent to whiten white fox and bluen blue fox respectively; S5. Drying.
2. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 1, characterized in that: In the degreasing step, the temperature is controlled at 40-45℃, and an ultrasonic generator is turned on to perform synchronous wave ultrasonic cleaning at a frequency of 25-28kHz, shortening the processing time to 1.5-2 hours.
3. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 1, characterized in that: In step S2, during the formaldehyde-free tanning process, while adding the zirconium-aluminum-plant polyphenol synergistic tanning agent, low-frequency ultrasonic treatment is activated. The ultrasonic frequency is 20~30kHz, and the treatment time is 30~60 minutes to promote the penetration of the tanning agent into the deep layers of the leather.
4. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance according to any one of claims 1 to 3, characterized in that: In step S2, the formaldehyde-free tanning process, the amount of salt added is 20-30 g / L, the amount of zirconium-aluminum-plant polyphenol synergistic tanning agent added is 8%-15% of the hide weight, and the amount of penetrant added is 0.5-1.0 g / L.
5. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 4, characterized in that: The zirconium-aluminum-plant polyphenol synergistic tanning agent is composed of the following components: Zirconium-based components are used to provide metal coordination ability; Aluminum-based components are used to form complexes with plant polyphenols and to regulate the tanning process; Plant polyphenol components, acting as cross-linking bridging molecules, connect metal ions and collagen; And a scavenging agent for controlling the hydrolysis rate of the zirconium-based component.
6. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 5, characterized in that: The mass ratio of the zirconium-based component, aluminum-based component, plant polyphenol component and scavenger is 2.0~3.0:0.8~1.5:2.0~4.0:0.5~1.
0.
7. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 6, characterized in that: The zirconium-based component is zirconium chloride or zirconium sulfate; the aluminum-based component is basic aluminum chloride or aluminum sulfate.
8. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 6, characterized in that: The plant polyphenol components are derived from at least one extract of green tea by-products, gallnut, or mulberry bark, and have a solid content >80%.
9. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 6, characterized in that: The masking agent is sodium citrate or sodium lactate.
10. The eco-friendly tanning process for fox fur based on formaldehyde-free synergistic tanning and ultrasonic assistance as described in claim 1, characterized in that: In step S3, the pyrethroid microcapsule content in the special fatliquoring agent is 5-8%; the specific parameters of the pulsed microwave assistance are: microwave frequency 2450MHz, intermittent pulse mode, and control of the skin plate temperature not exceeding 45℃.
Citation Information
Patent Citations
Tanning process for making fur from raw fox skins
CN105969919A